Development of Case-Based Learning Device with Cognitive Conflict Strategies to Improve the Critical Thinking Ability of Prospective Teacher Students - Yusup, Muhammad Yusril; Harjono, Ahmad; Makhrus, Muh (International Journal of Essential Competencies in Education, 2024)
This study aimed to develop and evaluate a Case-Based Learning (CBL) device incorporating cognitive conflict strategies to enhance the critical thinking abilities of prospective teacher students, a response to the global competitiveness challenge faced by Indonesian education. Through a methodological lens of research and development, the study meticulously validated a suite of educational devices, including lesson plans, student worksheets, teaching materials, and instruments designed to test critical thinking abilities. Additionally, the research scrutinized the practicality of these devices in actual classroom settings, ensuring their applicability in real-world educational environments. The findings from this comprehensive analysis revealed that the CBL device not only met the criteria for validity and reliability but also demonstrated significant practicality, as evidenced by its seamless integration and consistent application in classroom scenarios. A pivotal aspect of the study was the quantifiable enhancement in the critical thinking capabilities of the students involved, which was rigorously assessed through pretest and posttest measures. These assessments, underpinned by substantial effect sizes obtained via paired t-test analyses, highlighted a marked improvement in the critical thinking skills of the prospective teachers. The empirical evidence garnered through this research underscores the transformative potential of the CBL device, advocating for its widespread adoption in teacher education programs. The study posits that such an innovative educational device is quintessential for equipping future educators with the necessary skills to navigate and contribute effectively to the 21st-century educational landscape, thereby responding adeptly to the evolving demands of global educational competitiveness.